2015
DOI: 10.1002/rra.2937
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Streamflow Augmentation as a Short-Term Freshwater Mussel Conservation Strategy

Abstract: Recurrent and prolonged droughts, coupled with increased water resource demand, threaten freshwater mussel populations through stream drying and water quality degradation. Augmentation of stream discharge was proposed as a short-term strategy to maintain adequate streamflows and water quality in reaches with important freshwater mussel populations during exceptionally low flow periods. We investigated the effects of water augmentation on seven freshwater mussel species in a small creek between 2011 and 2014. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
(66 reference statements)
0
6
0
Order By: Relevance
“…In many prior mark-recapture studies with freshwater mussels, emigration has been assumed to be temporary and result from vertical migration into the substrate (Meador, Peterson, & Wisniewski, 2011;Villella et al, 2004;Wisniewski, Abbott, & Landis, 2016). However, in WNC, movement from study plots was likely to be permanent and result from mussels being displaced during high flows.…”
Section: Population Recoverymentioning
confidence: 99%
See 1 more Smart Citation
“…In many prior mark-recapture studies with freshwater mussels, emigration has been assumed to be temporary and result from vertical migration into the substrate (Meador, Peterson, & Wisniewski, 2011;Villella et al, 2004;Wisniewski, Abbott, & Landis, 2016). However, in WNC, movement from study plots was likely to be permanent and result from mussels being displaced during high flows.…”
Section: Population Recoverymentioning
confidence: 99%
“…Creek, GA, U.S.A. (Wisniewski et al, 2016). A 4-year mark-recapture study in the Cacapon River, WV, U.S.A., reported high adult survival rates (> 90%) across three species (Villella et al, 2004).…”
Section: Survival Analysismentioning
confidence: 99%
“…As it is becoming increasingly important to understand and monitor species-specific population dynamics for conservation management, the incorporation of CMR into mussel monitoring studies has steadily been expanding [25][26][27][29][30][31]71]. Similar to quadrat surveys, CMR is useful for estimating and detecting population trends, but in addition, it can: (1) offer improved precision in population parameter estimates; (2) provide reliable estimates of vital rates (i.e., survival, mortality, recruitment); (3) investigate factors influencing vital rates and detectability; and (4) be used to validate and improve species-specific demographic models-particularly for species occurring at lower densities [10,17,18,26,32].…”
Section: Overallmentioning
confidence: 99%
“…Differences in ability to detect individuals among surveyors can be attributed to years of experience, familiarity with target species or the study area, visual acuity, dedication, and mental or physical fatigue [26,27,29]. Although surveyor ability to detect adults at the substrate surface is often positively associated with increasing mussel shell length, CMR studies have demonstrated that this relationship can vary with substrate size and habitat type [26,27,31]. To make things more complex, many of these factors influencing availability and detectability can have interacting effects and vary by species.…”
Section: Overallmentioning
confidence: 99%
See 1 more Smart Citation